2011
DOI: 10.1159/000327021
|View full text |Cite
|
Sign up to set email alerts
|

Estimated Glomerular Filtration Rate in Short-Risk Stratification in Acute Myocardial Infarction

Abstract: Background/Aims: Renal dysfunction is associated with a higher risk of cardiovascular disease in patients with acute myocardial infarction (AMI). The aim of this study was to investigate the independent prognostic value of renal dysfunction and its incremental predictability risk after adjusting for well-known clinical factors in patients with AMI. Methods: 751 consecutive patients with AMI admitted to the Coronary Care Unit (CCU) were included. Patients were grouped into 2 categories according to the baseline… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 49 publications
1
11
0
Order By: Relevance
“…Therefore, our data suggest that a moderately reduced eGFR is associated with additional cardiac stress in patients with established heart disease. This assumption is in agreement with the negative prognostic impact of a reduced eGFR following acute myocardial infarction and in chronic heart failure patients [14,15,16]. The mechanisms underlying the proposed interaction between renal function and cardiac stress cannot be determined from our study.…”
Section: Discussionsupporting
confidence: 87%
“…Therefore, our data suggest that a moderately reduced eGFR is associated with additional cardiac stress in patients with established heart disease. This assumption is in agreement with the negative prognostic impact of a reduced eGFR following acute myocardial infarction and in chronic heart failure patients [14,15,16]. The mechanisms underlying the proposed interaction between renal function and cardiac stress cannot be determined from our study.…”
Section: Discussionsupporting
confidence: 87%
“…Due to its lipid-lowering effect, the ε2 allele has been considered protective against coronary artery disease. Impaired renal function/CKD has been related to the risk of suffering heart failure [31]. Recent studies have identified associations between gene variants and heart failure which could be explained by an effect on renal function [32].…”
Section: Discussionmentioning
confidence: 99%
“…Blasco et al . [ 25 ] evaluated 751 patients with acute MI admitted to a coronary care unit (CCU). Subjects with GFR lower than 60 ml/min/1.73m 2 were older, had greater comorbidities, congestive heart failure and higher mortality than those with GFR equal or greater than 60 ml/min/1.73m 2 .…”
Section: Discussionmentioning
confidence: 99%